Understanding Medicine Need Estimation within the Public Healthcare System in Iraq: A Review Article - Hasan A. Shubbar; Ali Azeez Al-Jumaili; Fadhel Ali Shihab; Mohammed Hameed Salih; Hadeer Akram Al-Ani (Iraqi Journal of Pharmaceutical Sciences, 2026)
The Iraqi medication management system comprises five key pillars: selection, need estimation, procurement, storage and distribution, and use. Despite the diligent efforts of pharmacists to accurately estimate medication needs, Iraqi public health institutions sometimes experience medication shortages due to inadequate budget allocations and procurement challenges. This review examines current practices, legislation, and challenges in the need estimation of medications. Indeed, there is significant collaboration among Iraqi health authorities responsible for medication approval, regulation, procurement, and dispensing. Key stakeholders, including the Directorate of Technical Affairs/Department of Need Estimation, Department of Pharmacy, KIMADIA, health directorates, and pharmacy and therapeutics committees in public health institutions collaborate to estimate annual medication needs. The methods for calculating needs include consumption, morbidity, and proxy methods, each with distinct advantages and limitations. The article highlights how morbidity data, medication consumption records, and medical employed protocols influence medication estimation processes. Obstacles hindering accurate estimation include inadequate electronic systems, inconsistent supply, expiring medications, population displacement, health crises (e.g., COVID-19), insurance implementation, and changes in prescribing practices. In conclusion, estimating medication needs in the public health sector is crucial for sustainable supply, but it is a complex task with multiple protocols and challenges. To enhance the effectiveness of medication, and need estimation in Iraq, the health system must prioritize electronic documentation and allocate sufficient budgets. By addressing these challenges, sustainable medication supply can be achieved in public healthcare settings.